New in The Tropical Agriculturalist series [1] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Market Gardening, by R. Kroll, CTA/Macmillan co-publication 1997, 176 pp., ISBN 0-333-65449-8, 10 credit points